Cost reduction associated with heparin-induced thrombocytopenia panel ordering for enoxaparin versus heparin for prophylactic and therapeutic use: A retrospective analysis in a community hospital setting - Menon, Harry; Pillai, Adip; Aussenberg-Rodriguez, Jeanine; Ambrose, John; Youssef, Irini; Griffiths, Elizabeth G; Al Ustwani, Omar (Avicenna Journal of Medicine, 2018)
Background: Most hospitals still use unfractionated heparin (UFH) as the primary agent for venous thromboembolism (VTE) prophylaxis in the hospital setting due to ease of use and insignificant cost. However, the risk of heparin-induced thrombocytopenia (HIT) has led some groups to favor other options for therapeutic and prophylactic anticoagulation. This is particularly relevant in light of recent data demonstrating a lower rate of HIT in patients receiving enoxaparin compared with UFH. This study examines the cost-effectiveness of enoxaparin, compared to UFH for prophylactic and therapeutic usage in hospitals. Methods: We conducted a retrospective chart review of patients who underwent HIT panel testing at the Inspira Health Network, Vineland campus (an approximately 262-bedded community hospital located in southern New Jersey that services a population of approximately 61,050) from the period of April 1, 2015 through December 31, 2016. The starting date represents the time from which enoxaparin became the primary alternative anticoagulant available at this hospital. Records of the total usage and cost of UFH and enoxaparin for the specified time period were collected from the hospital pharmacy database for evaluation, as were records of HIT panels. The information was analyzed to determine the frequency of HIT panel testing orders for patients receiving UFH versus those receiving enoxaparin. Annual cost-savings for the hospital were extrapolated using the comparative incidence of HIT panels and associated costs, including increased length of stay, hematology/oncology consultation, use of an alternative anticoagulant, critical bleeding requiring transfusion, and complications of HIT-associated thrombosis. These variables were multiplied by the incidence rate for each specified drug and usage to determine the daily cost for each drug. Results: The use of enoxaparin did not result in a significant decrease in the ordering of HIT panels in the hospital, with a relative rate ratio of 0.948 (95% confidence interval: 0.336, 2.21). When the data were stratified to examine prophylactic and therapeutic anticoagulation, there was a marked difference in the frequency of HIT testing. The rate ratio of HIT panel orders for patients receiving therapeutic enoxaparin rather than intravenous (IV) UFH was 0.118 (0.006, 0.625). These numbers were used to extrapolate the total daily cost of enoxaparin compared with IV UFH; therapeutic enoxaparin cost $30.66, while IV UFH cost $162.30. IV UFH use was associated with a higher incidence rate of HIT panel orders, and consequently a higher daily cost due to the likelihood of increased length of stay, use of alternative anticoagulation, bleeding requiring transfusion, and request for expert consultation. Conclusion: In this study, the use of enoxaparin was associated with a significant cost-saving over IV UFH when used for therapeutic anticoagulation, but this cost saving was not observed for prophylactic anticoagulation.
Keywords: Anticoagulation; heparin-induced thrombocytopenia; low molecular weight heparin